2021
DOI: 10.1210/clinem/dgab407
|View full text |Cite|
|
Sign up to set email alerts
|

The Cortisol and ACTH Response to Dex/CRH Testing in Women With and Without Perimenopausal Depression

Abstract: Background Abnormalities in the hypothalamic pituitary-adrenal (HPA) axis are frequent accompaniments of depression, and studies have documented the role of stress and stressful life events in the ontogeny of perimenopausal depressions (PMD). Since HPA axis function in women is further modulated by both aging and ovarian steroids, it is possible that a dysregulated HPA axis contributes to the increased risk of PMD. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…An experimental study ( 227 ) examined HPA axis function in perimenopausal women with and without current or past depression using the combined dexamethasone-corticotropin-releasing hormone (Dex/CRH) test. The two groups did not differ in either baseline or stimulated ACTH, nor cortisol secretion.…”
Section: The Role Of the Hpa Axis In Depression Across The Female Rep...mentioning
confidence: 99%
“…An experimental study ( 227 ) examined HPA axis function in perimenopausal women with and without current or past depression using the combined dexamethasone-corticotropin-releasing hormone (Dex/CRH) test. The two groups did not differ in either baseline or stimulated ACTH, nor cortisol secretion.…”
Section: The Role Of the Hpa Axis In Depression Across The Female Rep...mentioning
confidence: 99%
“…It has antidepressant-like effect, which may be related to the regulation of monoamine nerve transposition system in the brain ( 124 ). Contrary to the traditional idea, Guerrierieri GM ( 125 ) tested the HPA axis function of perimenopausal women with and without depression using the combined dexamethasone-adrenocorticotropin releasing hormone test. It was found that there was no inter-group difference in both baseline and stimulated ACTH and cortisol secretion.…”
Section: Prevalent Mechanisms Of Perimenopausal Depressionmentioning
confidence: 99%
“…Under the state of stress, the HPA axis is activated and stimulates the release of CRH from paraventricular hypothalamic nucleus neurons, then CRH induces the anterior pituitary gland to secrete ACTH. After ACTH enters the peripheral circulation system, it promotes adrenal cortex to produce CORT 25) . More serious HPA axis dysregulation has been observed in females under chronic stress, accompanied by the increase of ACTH and CORT levels 26) .…”
Section: Hormonesmentioning
confidence: 99%